GEORGE BERKOWSKI. - Tivnan, Tom (Bookseller, 2014)
The article presents an interview with application developer George Berkowski about publishing. Topics covered include the lessons that can be learned by publishing from the technology industry, the obstacles facing publishers in the digital age, and Berkowski's experience in publishing a book in a traditional manner.